EFICIENCIA ECONOMICA EL EN SECTOR EJIDAL DEL DISTRITO DE RIEGO NO 4 CIUDAD ANAHUAC NUEVO LEON - GUAJARDO Q, EAMON GPE; CHALITA TOVAR, LUIS EDUARDO; BARRERA ISLAS, DANIEL (Centro de Economía Agrícola, Colegio de Posgraduados, 1975)
si
AGRO
Keywords: EFICIENCIA ECONOMICA, SECTOR EJIDAL DEL DISTRITO DE RIEGO NO 4, CIUDAD ANAHUAC, NUEVO LEON; CIENCIAS AGRARIAS; INGENIERIA AGRICOLA; RIEGO